PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN DENGAN KERETA KARDUS PADA SISWA KELAS I SDN 67 BANDA ACEH - Ida Elva (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2019)
The study aims to improve the ability to read at the beginning of class I students of Public Elementary School 67 in Banda Aceh. This research is classroom action research (PTK) which consists of two cycles, each cycle consisting of three meetings and each meeting consists of four stages, namely planning, implementation, observation, and reflection. The subjects of this study were class I students of Public Elementary School 67 in Banda Aceh with a total of 28 students. This research was conducted in the odd semester (I) 2018/2019 academic year. Through the use of cardboard, train props can improve the ability to read the beginning of namely pre-cycle students who complete learning as much as 14 (50%) of 28 total students, then increase in the first cycle to 61% and in cycle II increased to 85% means that the level of students' abilities in reading beginning learners Pilot class I Public Elementary School 67 in Banda Aceh experienced increase a significant of pre-cycle up to the second cycle.